Teori Kebertakwaan Institusional: Integrasi Nilai Spiritual dalam Manajemen dan Tata Kelola Lembaga Keuangan Syariah: Institutional Taqwa Theory: Integrating Spiritual Values Into the Management and Governance of Islamic Financial Institutions - Ihwan Wahid Minu; Yusphan (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2026)
This article explores the limitations of secular earnings management theories, particularly those grounded in rational and self-interested motives such as Agency Theory, which are deemed insufficient within the Islamic economic framework. Using a conceptual and qualitative approach, this study aims to develop the Institutional Taqwa Theory as an alternative model that embeds spiritual values—especially taqwa—into institutional governance. The study integrates Islamic ethical principles, maqāṣid al-sharī‘ah, and spiritual accountability systems by critically engaging classical and contemporary literature while dialoguing conventional management theories with Islamic teachings. The findings reveal that this theory provides a novel conceptual framework for addressing earnings management in an ethical and spiritual manner. Furthermore, the study outlines measurable indicators of spiritual accountability and proposes practical instruments for evaluation, along with identifying opportunities for application within Islamic financial institutions. Its main contribution lies in constructing a normative and operational model based on transcendental values that bridges the gap between conventional accounting theories and Islamic principles in modern institutional practices.